Transcriptomic-based selection of reference genes for quantitative real-time PCR in an insect endosymbiotic model - Vallier, Agnès; Dell’Aglio, Elisa; Ferrarini, Mariana Galvão; Hurtado, Ophélie; Vincent-Monégat, Carole; Heddi, Abdelaziz; Rebollo, Rita; Zaidman-Rémy, Anna (Frontiers in Ecology and Evolution, 2023)
Reference genes are a fundamental tool for analyses of gene expression by real-time quantitative PCR (qRT-PCR), in that they ensure the correct comparison between conditions, stages, or treatments. Because of this, selection of appropriate genes to use as references is crucial for proper application of the technique. Nevertheless, efforts to find appropriate, stably expressed transcripts are still lacking, in particular in the field of insect science. Here, we took advantage of a massive transcriptomic high-throughput analysis of various developmental stages of the gut and associated-bacteriomes of the cereal weevil Sitophilus oryzae and identified a subset of stably expressed genes with the potential to be used as housekeeping genes from the larva to the adult stage. We employed several normalization techniques to select the most suitable genes among our subset. Our final selection includes three genes - TAO, YTH3 and PP12A - which can also be used to compare transcript abundance at various developmental stages in symbiotic insects, and in insects devoid of endosymbionts (aposymbiotic). Since they are well conserved, these genes have the potential to be useful for many other insect species. This work confirms the interest in using large-scale, unbiased methods for reference gene selection.